Effects of beetroot juice supplementation on agility in competitive female volleyball players - Moreno-Lara, J.; López-León, I.; Muñoz-Llerena, A.; Guzmán-Nebro, J. A.; Rico, E.; Sánchez-Oliver, A. J.; Muñoz-López, A.; Domínguez, R. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Inorganic nitrate (NO3-), which is abundant in some green leafy vegetables and beetroot, is sequentially reduced to nitrite (NO2-) and nitric oxide (NO) following ingestion. Dietary NO3- supplementation has been reported to have ergogenic effects on improving endurance (1), high intensity (2), and explosive efforts (3). However, the majority of the studies included only male athletes. The objective of this study was to analyse the influence of the acute supplementation with NO3rich beetroot juice (BJ) on the subsequent performance of professional female volleyball players agility ability.